REVIEW - Claudia-Ştefania Bala (Oncolog-Hematolog.ro)
Iron, ferroptosis and association with tumoral evolution and potential therapeutic impact Decision making in Merkel cell carcinoma – surgical oncologist point of view Cardiac toxicity of checkpoint inhibitors (CPI) used in cancer immunotherapy Immune-mediated complications of monoclonal antibodies used in onco-hematology